The Multifunctional Effects ofNiacinamide, Sodium Hyaluronate,and Hydrolyzed Collagen (Aintelia Science Notes, 2026)
Skin aging is characterized by moisture loss, a decrease in collagen, and a slowing of cellular renewal. During this process, structural and functional changes occur in the epidermis, dermis, and hypodermis layers. In this study, a multifunctional active complex containing hyaluronic acid, niacinamide, and hydrolyzed collagen was developed and incorporated into a facial serum at a 5% concentration. The formulation's efficacy was evaluated over a 4-week period on 20 female volunteers aged 25–39. Following the application of the serum twice daily, an increase in skin hydration and smoothness, as well as a reduction in dryness and the appearance of fine lines, was observed. The findings indicate that the developed active complex provides skin brightening and is effective in reducing signs of aging.
Keywords: Niacinamide; Sodium Hyaluronate